THE EFFECT OF KNOW, WANT, LEARNED (KWL) STRATEGY ON THE SECOND GRADE STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXTS AT SMPN 18 PEKANBARU - Amira, Natasa; Novitri, Novitri; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental study is aimed to find out whether there is significant effect of Know Want Learned (KWL) strategy on the second grade students’ reading comprehension on narrative texts at SMPN 18 Pekanbaru. The research design is a pre-experimental research with one group pre-test and post-test design. The sample was VIII.C chosen by using cluster random sampling technique. The result of the data analysis shows that the mean score of the pre-test is 64.49 and the mean score of the post test is 77.22. In other words, the mean score of post-test was higher than the pre-test. The result also shows that the value of t-test is higher than t-table (18,40 > 2.03) at significance level of 5%. Therefore, Alternative Hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. It can be concluded that there is significant effect of Know Want Learned (KWL) strategy on the second grade students’ reading comprehension on narrative texts at SMPN 18 Pekanbaru.Keywords: Effect, KWL, Reading Comprehension, Narrative Text